Pengaruh Model Pembelajaran Kooperatif Make a Match Terhadap Hasil Belajar Matematika Pada Materi Persamaan Linear Satu Variabel Peserta Didik di Kelas VII SMP Negeri Satap Ngarukahiri: Penelitian - Susanti Kahi Leba; Elsy Senides Hana Taunu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This research aims to determine the effect of the Make A Match learning model on students' mathematics learning outcomes in class VII lines and angles at Satap Ngarukahiri State Middle School in the Even semester of the 2025/2026 academic year. This type of research is quantitative experimental research with a One Group Pretest-Posttest design. The research subjects who were treated using the make A Match learning model were 21 class VII students. From the results of research and data analysis, test results were obtained on the sample t-test. Based on the results of the sample t-test carried out, it can be obtained that the sig. (2-tailed) 0.000, which means the value is less than 0.005 (0.000 < 0.005), so it can be concluded that H_1 is accepted and H_0 is rejected. So there is an influence of the Make A Match learning model on the mathematics learning outcomes of class VII students at Satap Ngarukahiri State Middle School.